Enhancing Concrete Sustainability with Self-Healing Technologies - Abdullatif, Al Shimaa (AUC Knowledge Fountain, 2024)
Thanks to its strength, durability and affordability, Portland cement concrete is the most commonly used building material worldwide. However, concrete cracking is inevitable due to numerous factors including shrinkage, exposure to external chemicals, internals reactions, excessive loads, to name but a few. Self-healing is a promising technique that can enable concrete to autogenously heal cracks and alleviate much of the damage. Such healing can without a doubt extend the service life with less need for external repair works therefore it contributes to sustainability. Over the years, several means of self-healing agents have been explored including bio-based procedures and the incorporation of mineral admixtures. Through the precipitation of carbonate-calcium rich materials, full or partial healing of cracks takes place. Since self-healing increases resilience and maintains performance with less maintenance, it becomes a core sustainability attribute. As cracks are main ingress routes for external attack, self-healing can significantly minimize deterioration due chemicals, chloride ion penetration which minimizes the corrosion of steel reinforcement. This is a pronounced to contribution to an enhanced concrete durability that lends itself to a set of environmental merits. This study aims at comparing and characterizing several concrete self-healing systems in order to assess quantitatively and qualitatively the healing process for each in order to help users to determine the need for a self-healing agent or to rely primarily on concrete intrinsic healing. To meet this objective, the intrinsic healing capacity of control mixtures is assessed and compared against conjugate mixtures made by incorporating self-healing. Various dosages of membrane-forming crystalline admixtures and sodium silicate will be directly added to concrete. To evaluate crack-filling, strength recovery, and permeability reductions, concrete samples will undergo mechanical, and durability testing. The test results herein reveal that, even with slight decreases in compressive strength, sodium silicate and crystalline admixtures considerably recover transport parameters like water intrusion and chloride penetration caused by crack-sealing. Interfaces healed by mineral precipitation are confirmed by the ultrasonic pulse velocity test results. The findings demonstrate that by repeatedly mitigating internal and external damage, these mineral admixtures can extend longevity. However, in general construction, commercial viability may be limited due to strength constraints. Enhancing the self-healing concrete by better balancing mechanical and durability-focused objectives will positively impact concrete in general and the elements exposed to outer environment in particular. Clearly, for the full performance and economic potential to be realized, further optimization and field implementations are required. One of the key findings of this work is that it contributes to better advance the understanding of the mechanisms by which self-healing concrete functions and provide better ability to select the healing approach. This paves the way for pinpointing recommendations for enhanced structural resilience and sustainability.